. - Hooft Lauterslager, Pedro Federico (Acta Bioethica, 2000)
The objective of this research is to analyze, from a bioethical and legal perspective, one of the particularly complex situations in which a woman -and her family- might find themselves in front of a diagnosis of anencephalic fetus, and to consider weather the decision of interrupting that pregnancy would or not be ethically justifiable.